2006
DOI: 10.1007/s00500-006-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Design and Application of Spiking Neural Networks

Abstract: This paper presents new findings in the design and application of biologically plausible neural networks based on spiking neuron models, which represent a more plausible model of real biological neurons where time is considered as an important feature for information encoding and processing in the brain. The design approach consists of an evolutionary strategy based supervised training algorithm, newly developed by the authors, and the use of different biologically plausible neuronal models. A dynamic synapse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 28 publications
(36 reference statements)
0
30
1
Order By: Relevance
“…The minimal classification error we obtained on the test data is 1.2%, which is a little better than those reported in [5] and [16], where the test error is 1.8% and 2.4%, respectively. Our results are also comparable to those of analog neural networks with two hidden layers [22], where the mean classification error on the test data is 1.15% and 2.87%, respectively, when direct connections between input and output nodes are present or absent.…”
Section: Results From Network With Single-terminal Connectionscontrasting
confidence: 65%
See 1 more Smart Citation
“…The minimal classification error we obtained on the test data is 1.2%, which is a little better than those reported in [5] and [16], where the test error is 1.8% and 2.4%, respectively. Our results are also comparable to those of analog neural networks with two hidden layers [22], where the mean classification error on the test data is 1.15% and 2.87%, respectively, when direct connections between input and output nodes are present or absent.…”
Section: Results From Network With Single-terminal Connectionscontrasting
confidence: 65%
“…In [13], an adaptive GA is adopted to evolve the weights of the SRM model for robot navigation, while in [14], a parallel deferential evolution has been employed to evolve the weights of the SRM. Both weights and delays of an integrate-and-fire (IAF) model with dynamic synapses [15] and a SRM are evolved using an evolution strategy [16]. It is found that the performance of the SNNs are comparable to that of the analog feedforward neural network on two benchmark problems.…”
Section: Introductionmentioning
confidence: 99%
“…Models of single neurons as well as computational SNN models, along with their respective applications, have been already developed [33,68,73,7,8,12], including evolving connectionist systems and evolving spiking neural networks (eSNN) in particular, where an SNN learns data incrementally by one-pass propagation of the data via creating and merging spiking neurons [61,115]. In [115] an eSNN is designed to capture features and to aggregate them into audio and visual perceptions for the purpose of person authentification.…”
Section: Evolving Spiking Neural Network and Neurogenetic Systems Fomentioning
confidence: 99%
“…-Moving object recognition [26]; -EEG and fMRI data modelling and pattern recognition [27,47] (fig.8); -Robot control through EEG signals (www.kedri.info, fig.9) and robot navigation [2]; -Sign language gesture recognition (e.g. the Brazilian sign language [ ]; -Risk of event evaluation, e.g.…”
Section: Current and Future Applications Of Esnn For Stprmentioning
confidence: 99%